Effects of acute carbohydrate supplementation on endurance performance: A meta-analysis - Vandenbogaerde, T. J.; Hopkins, W. G. (Sports Medicine, 2011)
Research on the performance effects of acute carbohydrate supplementation is comprehensive. Here we present the first meta-analytic review of this research.